On Certain Factors of Uniformity of Judicial Practice - G. A. Borisov (Сибирское юридическое обозрение)
The article presents a study of modern factors that influence the shaping of uniform judicial practice in various countries of the world. The system of ensuring legal certainty established in the Russian Federation is regarded as superior to the system of stare decisis, whose proponents not infrequently seek stability for the sake of stability. A conclusion is drawn that abstract interpretation, not tied to the particular circumstances of an individual dispute, not having a strictly obligatory nature, and issued by a collective body of the apex court leaves more room for judicial discretion and orientation on legal principles. Trends are discovered in the court structure and rules of court procedure in foreign countries, indicating the continuing competition between the two systems, as well as a search for their synthesis. An opinion is put forward that lowering judicial workload through cutting-edge technologies, including artificial intelligence, is one of the keys to increasing the quality of justice. In this regard, potential risks and benefits of introducing those technologies into court activities are considered. The example of Chinese courts is used to illustrate the danger of lending too much importance to the recommendations of AI algorithms; a suggestion is formulated to introduce a new function into the prospective “Justice Online” superservice. Particular attention is paid to such subjective factors as judicial workload and judicial well-being, their role for the work of the courts. Based on foreign research and a report presented by the UN Office on Drugs and Crime, a conclusion is made about the importance of maintaining the physical and psychological well-being of judges for ensuring the proper quality of court decisions. The importance of dialog and exchange of best practices in the sphere of judicial well-being is stressed, various problems arising as a result of turning a blind eye to this sphere are considered. In conclusion, the importance of studying the results of work of the top judicial body in ensuring uniform judicial practice is emphasized, as well as that of dissemination of information about the adopted legal standings among the general public.